2009
DOI: 10.1016/j.ccr.2009.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Transformation of Adult Pancreatic Cells by Oncogenic K-Ras

Abstract: Summary Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal human malignancies. To investigate the cellular origin(s) of this cancer, we determined the effect of PDAC-relevant gene mutations in distinct cell types of the adult pancreas. We show that a subpopulation of Pdx1-expressing cells is susceptible to oncogenic K-Ras induced transformation without tissue injury, whereas insulin-expressing endocrine cells are completely refractory to transformation under these conditions. However, chronic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
260
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(278 citation statements)
references
References 54 publications
16
260
0
2
Order By: Relevance
“…Additionally, a recent study highlighted this tumorigenic mechanism in a model of pancreatic cancer. In that model, certain cell populations were refractory to transformation until exposed to an inflammatory environment generated by wounding (55). This raises the question of whether a tumorigenic load exists that can drive cancer formation in the Shh-expressing hair follicle TA population and represents a direction for future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent study highlighted this tumorigenic mechanism in a model of pancreatic cancer. In that model, certain cell populations were refractory to transformation until exposed to an inflammatory environment generated by wounding (55). This raises the question of whether a tumorigenic load exists that can drive cancer formation in the Shh-expressing hair follicle TA population and represents a direction for future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…5) suggest that aberrant expression of LRH-1 might be linked to proliferation of dedifferentiated pancreatic cancer cells, which are associated with aggressive pancreatic tumors (37). Recent studies demonstrated the inherent plasticity of pancreatic cells that can be reprogrammed to the transient dedifferentiated progenitor-like states, which can give rise to PDAC (38)(39)(40). Because of the established roles of LRH-1 in pancreatic and stem cell differentiation (7-9, 20), we hypothesize that this receptor might contribute to the reprogramming events in the adult pancreas that lead to its transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion or homozygous inactive mutations in PDX1 is lethal in mice due to whole pancreatic agenesis (2,3). Conditional knockout of PDX1 gene in β cells leads to overt diabetes, whereas knockingdown of PDX1 expression results in decreased insulin secretion in mice (4). PDX1 mutant zebrafish also exhibit several key diabetic features including reduced β cell mass, decreased insulin and elevated glucose levels.…”
Section: Pdx1 and Pdx1 Involved Diseasesmentioning
confidence: 99%